Severe Facet Joint Arthrosis Caused C7/T1 Myelopathy: A Case Report. (16th June 2009) - Aizawa, Toshimi; Ozawa, Hiroshi; Hoshikawa, Takeshi; Kusakabe, Takashi; Itoi, Eiji
Abstract : Cervical myelopathy is caused by degenerative processes of the spine including intervertebral disc herniation and posterior spur usually developing at C3/4 to C5/6. C7/T1 single level myelopathy is very rare because of the anatomical characteristics. Facet joint arthrosis can be a cause of cervical myelopathy but only a few cases have been reported. The authors report an extremely rare case of C7/T1 myelopathy caused by facet joint arthrosis. A 58-year-old male presented with hand and gait clumsiness. The radiological examinations revealed severe C7/T1 facet joint arthrosis with bony spur extending into the spinal canal, which compressed the spinal cord laterally. The T1 spinous process indicated nonunion of a "clay-shoveler's" fracture, which suggested that his cervico-thoracic spine had been frequently moved, and thus severe arthrosis had occurred in the facet joints. A right hemilaminectomy of C7 and C7/T1 facetectomy with single level spinal fusion led to complete neurological improvement.